2022
DOI: 10.3389/fpls.2022.922343
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Fusarium oxysporum GW controlling weed and an effective biostimulant for wheat growth

Abstract: Wheat crop has to compete with several weeds including Avena fatua, a noxious weed that alone is responsible for 30–70% losses in the yield annually. Because of the environmental concerns associated with conventional methods, researchers are on a continuous hunt to find clean alternatives in order to manage weeds. Fungi have shown promising weedicide potential in lab studies. The current study aimed to isolate endophytic fungi from wheat plants which can promote wheat growth and inhibit the growth of common we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 50 publications
(51 reference statements)
0
11
0
Order By: Relevance
“… Asim et al. (2022) observed increased root and aerial biomass, root and stem length, vigor index, and germination using wheat ( Triticum aestivum ) and endophytic fungus Fusarium oxysporum ( Asim et al., 2022 ; Poveda et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Asim et al. (2022) observed increased root and aerial biomass, root and stem length, vigor index, and germination using wheat ( Triticum aestivum ) and endophytic fungus Fusarium oxysporum ( Asim et al., 2022 ; Poveda et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“… Asim et al. (2022) observed increased root and aerial biomass, root and stem length, vigor index, and germination using wheat ( Triticum aestivum ) and endophytic fungus Fusarium oxysporum ( Asim et al., 2022 ; Poveda et al., 2022 ). It has also been reported that inoculating plants with S. indica or Arbuscular mycorrhizal fungi (AMF) boosts photosynthetic efficiency by increasing the chlorophyll content of leaves, surface area of leaves, stomatal conductance, and sugar content of leaves ( Das et al., 2012 ; Baishya et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The biological control agents generally used are fungi, because of their destructive properties, mass production, direct formulation, and direct applications (Hyde et al, 2019). One of the biological control fungi for weeds is Fusarium oxysporum (Soesanto et al, 2020;Asim et al, 2022) and Curcularia lunata (Li et al, 2013). Both fungi have received special attention in biological weed management.…”
Section: Introductionmentioning
confidence: 99%
“…Annually, up to 15–20% of agricultural yield losses are caused by fungal-associated diseases worldwide [ 1 , 2 ]. Wheat ( Triticum aestivum L.) is one of the most economically important crops in the world [ 3 ], but unfavorably, wheat is highly susceptible to fungal infections. Fusarium and Alternaria fungi are responsible for prominent infections of various crops, including summer and winter wheat [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to fungal infection processes, remaining crop debris above and below the soil can harbor pathogenic fungi and support their development and sporulation, and offer them a habitat to overwinter [ 10 , 14 , 15 , 16 , 17 , 18 ]. Arable weeds were often underestimated, but are now recognized to play a major role in the inoculation of crops with pathogenic filamentous fungi [ 3 , 10 , 16 , 19 , 20 , 21 , 22 , 23 ]. They offer a broad host range for fungal pathogens, including Fusarium and Alternaria , and can act as both alternative and alternate hosts for these species [ 24 ].…”
Section: Introductionmentioning
confidence: 99%